Spiro‐Carbon: A Metallic Carbon Allotrope Predicted from First Principles Calculations. Issue 1 (9th December 2019) - Oliveira, Felipe L.; Capaz, Rodrigo B.; Esteves, Pierre M.
Abstract: A structurally stable microporous metallic carbon allotrope, poly(spiro[2.2]penta‐1, 4‐diyne) or, for short, spiro‐carbon, with I41 /amd (D4h ) symmetry is predicted by first‐principles calculations using density functional theory (DFT). The calculations of electronic, vibrational, and structural properties show that spiro‐carbon has lower relative energy than other elusive carbon allotropes such as T‐Carbon and 1‐diamondyne (Y‐Carbon). Its structure can be pictured as a set of trans‐cisoid ‐polyacetylene chains tangled and interconnected together by sp 3 carbon atoms. Calculations reveal a metallic electronic structure arising from an "intrinsic doping" of trans‐cisoid ‐polyacetylene chains with sp 3 carbon atoms. Possible synthetic routes and various simulated spectra (XRD, NMR, and IR absorption) are provided in order to guide future efforts to synthesize this novel material. Abstract : New carbon allotrope : DFT calculations of a nanoporous allotropic carbon structure, named Spiro‐Carbon, which is, to the best of our knowledge unpublished in the literature. The calculations show that the new presented structure corresponds to a minimum on potential energy surface and has lower relative energy than other allotropic forms of carbon, such as T‐Carbon and Y‐Carbon, and presents a metallic electronic structure.